Examining the Exposure, Timing, and Frequency of Interpersonal Communication Contacts to Improve Infant and Young Child Feeding in Bangladesh, Ethiopia, and Vietnam (P10-138-19). (13th June 2019) - Kim, Sunny; Nguyen, Phuong; Tran, Lan; Alayon, Silvia; Menon, Purnima; Frongillo, Edward
Abstract: Objectives: In the context of large-scale interventions to improve infant and young child feeding (IYCF) practices, we examined differences in characteristics of those exposed and not exposed to interventions; exposure to interpersonal communication (IPC), including overlap with other interventions and timing and number of contacts; and relationship between frequency of IPC contacts and IYCF practices. Methods: We used endline survey data from Bangladesh (2000 mothers with children <2y, 1000 per program group), Ethiopia (1720 mother with children aged 6–23.9 mo, 1360 per group), and Vietnam (2005 mothers with children <2y, 1000 per group). Regression models were used to test differences in exposure to specific or combined interventions between two arms and relationships between the frequency of IPC contacts or exposure to interventions and IYCF practices, adjusted for child age and sex and geographic clustering. Results: Those exposed to interventions had higher socioeconomic status, food security, and maternal dietary diversity. There was large overlap in exposure to IPC with other interventions in intensive-intervention areas in all 3 countries. On average, mothers received 8 visits in the last 6 mo, 2 visits in the last 3 mo, and 1 visit in the last 6 mo in Bangladesh, Ethiopia, and Vietnam respectively. In Bangladesh, there was a positive, nonsignificant association between intervention exposure and IYCF practices in intensive areas. In Ethiopia, exposure to IPC with other interventions was associated with higher odds of minimum meal frequency (OR: 1.6), minimum dietary diversity (OR: 1.8), and consumption of iron-rich foods (OR: 4.7). In Vietnam, exposure to IPC alone or with mass media was associated with 3.7 and 2.8 higher odds respectively of exclusive breastfeeding. At least monthly visits was associated with higher odds of IYCF practices in Bangladesh and Ethiopia. In Vietnam, any number of IPC visits was associated with 2 times higher odds of exclusive breastfeeding. Conclusions: Effects of combined behavior-change interventions and frequency of IPC contacts may be context-specific. Funding Sources: Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI 360; and CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), led by the International Food Policy Research Institute.